Hepatoprotective effect of ethanolic extract of Trichosanthes lobata on paracetamol-induced liver toxicity in rats - Rajasekaran Aiyalu; Periyasamy Muthusamy (BMC, 2012)
Abstract Background Trichosanthes lobata (family cucurbitaceae) is used to treat malarial fever and liver disorders. This study aims to investigate possible hepatoprotective activities of ethanolic extract of Trichosanthes lobata against paracetamol-induced hepatotoxicity. Methods Hepatotoxicity was induced in Wistar male rats by oral administration, 2 g/kg body weight on 7th day after the administration of ethanolic extract of Trichosanthes lobata and silymarin (100 mg/kg). Ethanolic extract of Trichosanthes lobata was administered orally at doses of 200 mg/kg and 400 mg/kg body weight daily for 7 days. Several serum markers, aspartate transaminase, alanine transaminase, alkaline phosphatase, bilirubin, total protein was measured to assess the effect of the extract on paracetamol (acetaminophen)-induced hepatic damage. The study included histopathological examination of liver sections. Results Blood samples from rats treated with ethanolic extract of Trichosanthes lobata (200 mg/kg body weight and 400 mg/kg body weight) had significant reductions in serum markers in paracetamol administered animals, indicating the effect of the extract in restoring the normal functional ability of hepatocytes. Silymarin (100 mg/kg, p.o.) was used as a reference drug. Conclusion The ethanolic extract of Trichosanthes lobata exhibits protective effects against paracetamol‒induced hepatotoxicity.